Impact of crude-oil price volatility on economic activities: An empirical investigation in the Thai economy - Rafiq, Shuddsattwa; Salim, Ruhul; Bloch, Harry (Pergamon, 2008)
This paper empirically examines the impact of oil price volatility on key macroeconomic indicators of Thailand. Following Andersen et al. [2004. Analytical evaluation of volatility forecasts. International Economic Review 45(4), 1079-1110], quarterly oil price volatility is measured by using the realized volatility (RV). The impact of the oil price volatility is investigated using the vector auto-regression (VAR) system. The Granger causality test, impulse response functions, and variance decomposition show that oil price volatility has significant impact on macroeconomic indicators, such as unemployment and investment, over the period from 1993Q1 to 2006Q4. Perron's [1997. Further evidence on breaking trend functions in macroeconomic variables. Journal of Econometrics 80(2), 355-385] test identifies structural breaks in all the concerned variables during the time of the Asian Financial Crisis (1997-1998). A VAR for the post-crisis period shows that the impact of oil price volatility is transmitted to budget deficit.The floating exchange rate regime introduced after the crisis may be the key contributor to this new channel of impact.